Zur Systematik der Gattung Trioxys Haliday (Hymenoptera: Braconidae, Aphidiinae). - Mackauer, Manfred (Contributions to Entomology = Beiträge zur Entomologie, 1960)
In the above publication the author makes an attempt to divide the hitherto known species of the genus Trioxys Haliday 1833 (Hymenoptera : Braconidae, Aphinto groups of natural relationship. With special reference to morphologic and ecologic characters, Trioxys Haliday is divided into 4 subgenera: Betuloxys n. subgen., Binodoxys n. subgen., Trioxys Haliday 1833 s. s., and Pectoxys n. subgen. The hitherto subgenus Acanthocaudus Smith 1944 must get the rank of a separate genus. There are described as new: Trioxys angelicae mediterraneus n. ssp., T. bicuspis n. sp., T. n. sp., T. hincksi n. sp.,T. humuli n. sp., and the male of T. compressicornis Ruthe 1859. second description is given for the dubious species T. letifer (Haliday 1833) together with the fixation of a neotype. The name Trioxys obscuriformis Quilis 1940, invalid according to the International Rules of Zoological Nomenclature, is replaced by Trioxys fossilis n. n. The species Trioxys basilewskyi Benoit 1955 is transferred to the genus Paraphidius Stary 1958. Nomenclatural Acts basilewskyi (Benoit, 1955) (Paraphidius), comb. n. hitherto Trioxys basilewskyi Benoit, 1955 Betuloxys Mackauer, 1960 (Trioxys), sgen. n. Binodoxys Mackauer, 1960 (Trioxys), sgen. n. fossilis Mackauer, 1960 (Trioxys), nom. n. pro Trioxys obscuriformis Quilis, 1940, nec Quilis, 1931 genistae Mackauer, 1960 (Trioxys (Binodoxys)), spec. n. letifer (Haliday, 1833) (Trioxys (Binodoxys)), Neotype described as Aphidius (Trioxys) letifer Haliday, 1833 mediterraneus Mackauer, 1960 (Trioxys (Binodoxys) angelicae), sspec. n. bicuspis Mackauer, 1960 (Trioxys (Trioxys)), spec. n. hincksi Mackauer, 1960 (Trioxys (Trioxys)), spec. n. humuli Mackauer, 1960 (Trioxys (Trioxys)), spec. n.